Neuroimaging and clinical outcomes of oral anticoagulant–associated intracerebral hemorrhage. Issue 5 (25th October 2018) - Tsivgoulis, Georgios; Wilson, Duncan; Katsanos, Aristeidis H.; Sargento‐Freitas, João; Marques‐Matos, Cláudia; Azevedo, Elsa; Adachi, Tomohide; von der Brelie, Christian; Aizawa, Yoshifusa; Abe, Hiroshi; Tomita, Hirofumi; Okumura, Ken; et al.
Abstract : Objective: Whether intracerebral hemorrhage (ICH) associated with non–vitamin K antagonist oral anticoagulants (NOAC‐ICH) has a better outcome compared to ICH associated with vitamin K antagonists (VKA‐ICH) is uncertain. Methods: We performed a systematic review and individual patient data meta‐analysis of cohort studies comparing clinical and radiological outcomes between NOAC‐ICH and VKA‐ICH patients. The primary outcome measure was 30‐day all‐cause mortality. All outcomes were assessed in multivariate regression analyses adjusted for age, sex, ICH location, and intraventricular hemorrhage extension. Results: We included 7 eligible studies comprising 219 NOAC‐ICH and 831 VKA‐ICH patients (mean age = 77 years, 52.5% females). The 30‐day mortality was similar between NOAC‐ICH and VKA‐ICH (24.3% vs 26.5%; hazard ratio = 0.94, 95% confidence interval [CI] = 0.67–1.31). However, in multivariate analyses adjusting for potential confounders, NOAC‐ICH was associated with lower admission National Institutes of Health Stroke Scale (NIHSS) score (linear regression coefficient = −2.83, 95% CI = −5.28 to −0.38), lower likelihood of severe stroke (NIHSS > 10 points) on admission (odds ratio [OR] = 0.50, 95% CI = 0.30–0.84), and smaller baseline hematoma volume (linear regression coefficient = −0.24, 95% CI = −0.47 to −0.16). The two groups did not differ in the likelihood of baseline hematoma volume < 30cm 3 (OR = 1.14, 95% CI = 0.81–1.62), hematoma expansion (OR = 0.97, 95% CI = 0.63–1.48), in‐hospital mortality (OR = 0.73, 95% CI = 0.49–1.11), functional status at discharge (common OR = 0.78, 95% CI = 0.57–1.07), or functional status at 3 months (common OR = 1.03, 95% CI = 0.75–1.43). Interpretation: Although functional outcome at discharge, 1 month, or 3 months was comparable after NOAC‐ICH and VKA‐ICH, patients with NOAC‐ICH had smaller baseline hematoma volumes and less severe acute stroke syndromes. Ann Neurol 2018;84:702–712